Eternal Contemporaneity in Advertisements of „Naujoji Romuva“ (1931–1940) - Bankauskaitė-Sereikienė, Gabija; Keturakienė, Eglė (Respectus Philologicus, 2014)
Advertising appealing to senses is satiated with the dream of immortality. The society striving for an eternal state of mythical youth lives in the reality of theatre and manipulations. On the one hand, advertising offers certain society life models through myth, archetypical symbols. On the other hand, culture of global observation, watching changes life into an illusion and life simulation. The more a person succumbs to abstractedness of life in advertisements, the greater demand for mythical time, eternal moment and harmony arises. Advertising which has categorically prohibited for a society to get older, gives an individual an illusion of eternal contemporaneity through archetypes. Modern man sees himself as a creator of history, hence, he feels great temptation to take part in an imaginary act of creation. The article provides the analysis of archetypac imagery in interwar advertisements on the basis of insights of R. Barthes, G. Debord and M. McLuhan on mythological structures of thinking, advertisements and modern society of a performance as well as thoughts of M. Eliade on repetition of time. For the analysis publication Naujoji Romuva (1931-1940) has been chosen. The expression of archetypes has been discussed after they have been categorized into three groups under character and general context of archetypal structures: archetypes of world creation, prototypes of man and woman, and mythical, folklore. Prototypes of man as a hero and woman as having a mystic role to continue the cycle of life, as well as mythical, folklore symbols (mirror, horseshoe, spruce, flower) also play the said role. Archetypal imagery is often found in advertisements of cosmetics, chemicals and sealants.
Keywords: myth; symbol; archetype; repetition; time; advertising